Tumour budding is associated with the mesenchymal colon cancer subtype and RAS/RAF mutations: a study of 1320 colorectal cancers with Consensus Molecular Subgroup (CMS) data. Issue 10 (13th November 2018) - Trinh, Anne; Lädrach, Claudia; Dawson, Heather; Hoorn, Sanne; Kuppen, Peter; Reimers, Marlies; Koopman, Miriam; Punt, Cornelis; Lugli, Alessandro; Vermeulen, Louis; Zlobec, Inti
Abstract Background Tumour budding is an important prognostic factor in colorectal cancer (CRC). Molecular profiling of tumour buds suggests (partial) epithelial–mesenchymal transition and cancer stem-cell phenotype, similarly described in the "mesenchymal" Consensus Molecular Subtype 4 (CMS4), which identifies a particularly poor prognostic subgroup. Here, we determine the association of tumour budding with CMS classification, prognosis, and response to therapy. Methods AMC-AJCCII-90 cohort (n  = 76, stage II) was evaluated for peritumoural budding on H&E slides. LUMC (n  = 270, stage I–IV), CAIRO (n  = 504, metastatic CRC) and CAIRO2 (n  = 472, metastatic CRC) cohorts were investigated for intratumoural budding using pan-cytokeratin-stained tissue microarrays. Budding was scored as count/area, then classified as <5 or ≥5 buds. For all cohorts, CMS classifications were available (gene-expression/immunohistochemistry-based classifiers). Results High (≥5) budding predicted a worse outcome in multivariate analysis in AMC-AJCCII-90 (p  = 0.018), LUMC (p  < 0.0001), and CAIRO (p  = 0.03), and in CAIRO2 (continuous variable, p  = 0.02). Tumour budding counts were higher in CMS4 compared to epithelial CMS2/3 cancers (p  < 0.01, all), and associated withKRAS/BRAF mutations (p  < 0.01, AMC-AJCCII-90, CAIRO, CAIRO2). Conclusion Tumour budding is an adverse prognostic factor across all CRC stages and is associated with the mesenchymal CMS4 phenotype.KRAS/BRAF mutations are strongly correlated with tumour budding suggesting their involvement in the regulation of this process.